Treatment of Complex Dissociative Disorders: A Comparison of Interventions Reported by Community Therapists versus Those Recommended by Experts. Issue 1 (1st January 2015) - Myrick, Amie C.; Chasson, Gregory S.; Lanius, Ruth A.; Leventhal, Barry; Brand, Bethany L.
Abstract : There is a paucity of empirical data to assist clinicians in choosing interventions to use with patients with complex dissociative disorder (DD; i.e., dissociative identity disorder and dissociative disorder not otherwise specified) at different stages in treatment. This study compared interventions used by a sample of international outpatient therapists treating DD clients in the 1st 2 stages of treatment with those recommended by expert DD therapists. There were many similarities between therapists' and experts' interventions, including the use of several emotion regulation and dissociation-focused interventions. However, community therapists reported significantly less focus on relationally oriented interventions, teaching and using grounding and containment skills, and stabilizing patients after revictimization by alleged perpetrators. This study has important implications for the development and implementation of training opportunities for DD therapists.